The effects of biopsy and cryopreservation by vitrification on the in vitro development of eight-cell mouse embryos - Abdullah, Ramli; Mohamed Said, M.S.; Nor Ashikin, M.N.K.; Dzulsuhaimi, D.; Rajikin, M.H.; Mohamed, Z.; Faizah, S. (2006)
In vitro and in vivo development of cryopreserved and non-cryopreserved biopsied 8-cell mouse embryos were examined in this study. It was observed that intact and biopsied embryos could successfully be cryopreserved by using the blastomere biopsy and vitrification procedure. However, in vitro survivability of the embryos declined steadily with advancing developmental stages, irrespective of the treatments used. Overall, one-blastomere biopsy without cryopreservation yielded the highest rate of development to morula (96.1%), expanded blastocyst (84.3%) and hatched blastocyst (74.5%), respectively. When the effect of cryopreservation was taken into account, two-blastomere biopsy did not differ significantly from that of the one-blastomere biopsy in terms of development to the expanded and hatched blastocyst stages. The results of our study suggest that the two-blastomere biopsy with cryopreservation is a better option in the current set-up.